Periodic Differential Operators - Brown, B. Malcolm; Eastham, Michael S.P.; Schmidt, Karl Michael; SpringerLink (Online service) (Basel : Springer Basel : Imprint: Birkhäuser, 2013)
Periodic differential operators have a rich mathematical theory as well as important physical applications. They have been the subject of intensive development for over a century and remain a fertile research area. This book lays out the theoretical foundations and then moves on to give a coherent account of more recent results, relating in particular to the eigenvalue and spectral theory of the Hill and Dirac equations. The book will be valuable to advanced students and academics both for general reference and as an introduction to active research topics.
Preface -- 1 Floquet Theory -- 2 Oscillations -- 3 Asymptotics -- 4 Spectra -- 5 Perturbations.
Keywords: Mathematics; Operator theory; Differential Equations; Mathematics; Ordinary Differential Equations; Operator Theory